Realizacja kultu pamięci bliskiej osoby zmarłej w zakresie decydowania o sposobie pochówku osoby pozostającej w związku partnerskim - Haberko, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The text includes a discussion of the cult of the deceased which can be manifested by deciding on the funeral and the place of burial. The problem relates to a decision about the place of burial of the deceased, who remained in a partnership (whether it is a concubinage or homosexual), while the partner and the family do not agree in the matter. The author analyses the issue in the context of decision-making powers in the light of the Law on cemeteries and burials taking in consideration the debts of the succession. The problem is particularly evident when the deceased has not left a will, and between those who want to pursue the cult of the memory is a difference of opinion how this cult should be manifested. Another problem is a priority in this regard. It should be determinated where the deceased cohabitant or partner has to be buried, in what rite the funeral should be done or how his tombstone should look like. The text includes four possible situations of the cult of the deceased, taking into account the decision of the funeral
Keywords: cult of the memory; died close person; partner; burial